The Science and Practice of Rugby Training - Hamlin, Michael (Cambridge Scholars Publishing, 2024)
This book links the increasingly important science behind the training and recovery of rugby players with easy to understand and practical examples of how this knowledge can be implemented on the training field or in the gym. The book is unique in the way that it outlines simple tools and techniques to improve rugby player performance. The book covers the latest scientific evidence on common training practices and theories and sums up their practical use for rugby players. The book will be an invaluable resource for those interested in the scientific training approach to team sport players including coaches, strength and conditioning personnel, physiotherapists, and sport doctors along with students and sports enthusiasts. In addition, while the practical examples used in the book are specific to rugby players, the scientific knowledge within the book would be useful to many athletes and coaches thereby increasing the scope of the book to many sports